Comparison and validation of turbulence models in the numerical study of heat exchangers - Ardila Marín, Juan Gonzalo; Hincapié Zuluaga, Diego Andrés; Casas Monroy, Julio Alberto (TECCIENCIA, 2015)
This study aims to validate numerical models for heat exchangers developed with the commercial package ANSYS®, comparing the results with data published in the literature. The methodology was based on the identification of programs, languages, mathematical models, and numerical models used by other researchers. Geometries were developed with SolidEdge® and DesignModeler®, discretization meshes with Meshing®, and subsequent configuration of standard k-ɛ and k-ω models with Fluent® and CFX®. For internal flow in concentric smooth straight tube exchangers, we recreated the predicted results with Nusselts varying between 100 and 250 and Reynolds regimes between 12*103 and 38*103. The study of internal flow in the curved corrugated tube exhibited considerable approximation to the results predicted by Zachar’s numerical correlation with Nusselt numbers in the range of 15-70 for Dean variations between 1*102 and 11*102 in laminar flow. Likewise, we validated the study of external flow in twisted curved tubes. Finally, Nusselt variations between 60 and 275 for Dean variations between 1*103 and 9*103 were modeled for completely developed laminar, transitional, and turbulent flow. The study shows the increase of heat flux associated with the change in the geometry of heat exchangers. It also demonstrates how numerical computer models can recreate realistic process conditions and thermo-fluid simulation by appropriately configuring systems.